Participatory local governance and cultural practices in Thailand - Gertrud Buchenrieder; Thomas Dufhues; Insa Theesfeld; Mungkung Nuchanata (Cogent Social Sciences, 2017)
How do cultural practices influence the process of participatory governance within local administrative structures? We address this question by reflecting cultural dimensions, such as collectivism, uncertainty avoidance, and power distance within a contextual sensitive “cultural sensemaking” model. The modelled context refers to community development meetings held in Thai communities. Here people gather to discuss development plans, which are later finalized at the Tambon Administrative Organization (TAO). We hypothesize that cultural practices influence action by giving the people the rules for action. The analysis of culture in the context of these meetings is an interpretive one and involves qualitative observation of and structured interviews. Our results show that the prevailing cultural practices do not promote truly transparent and open discussions as ascribed to participatory governance tools. Consequently, local leaders employ a subtle paternalistic leadership style. Yet, cultural practices change towards a more open and participatory rural society.
Keywords: 330; cultural practices; governance; participatory decision-making; local government; Thailand